An Epidemic of Mumps Reported in a Peripheral Charitable Hospital, Bengaluru, Karnataka - Sreepriya Lalitha; Minnie R (Pediatric Infectious Disease)
Mumps is a highly contagious, vaccine-preventable disease. It is one of the oldest human illnesses known to humans. Mumps is caused by paramyxovirus, which is a single-stranded ribonucleic acid (RNA) virus. It is a self-limited illness. Diagnosis is mainly clinical. Although infrequent in countries with extensive vaccination programs, mumps remains endemic in the rest of the world, warranting continued vaccine protection. Compared to other vaccine-preventable diseases, mumps is more benign. Consequently, topics relating to mumps have been somewhat neglected. Through this article, we are suggesting a wider range of protection through the measles, mumps, and rubella (MMR) vaccine to the susceptible population.